MODERN APPROACHES TO FALLS PREVENTION IN ELDERLY PERSONS - Kljajić, Dragana; Trajkov, Marija; Grbić, Gordana; Pantović, Ana; Stevanović, Kristina (HEALTH CARE, 2024)
Aging leads to the decrease in functional abilities, which affects the occurrence of falls that can often lead to disability. The aim of this review article is to analyze the contemporary approaches within the framework of measures for the prevention and control of falls in elderly persons. Published scientific works from the period 2003-2023 were used as data sources.Therapeutic exercises applied during rehabilitation and post-rehabilitation form the basis of good postural stability. Various systematic exercise programs have a significant place, but they need to be evidence-based and precisely applied. With the development of technology, several different methods and equipment are becoming available that can be used in the prevention of falls in a modern way. Robotic systems, applications, portable hardware devices, virtual reality equipment, as well as fall detection and prevention systems are just some of the newer technologies used in fall prevention. A multidisciplinary approach, which refers to the provision of information, teamwork of experts from different fields and monitoring of new technologies, could significantly contribute to the prevention of falls and improvement in the quality of life of the elderly.